Threaditional - See, Vanessa Yeu Chinq (Nanyang Technological University, 2020)
The significant rise in the number of interracial marriages since 20 years ago, has sparked the idea of fusion, signifying the union of the couple. It takes a huge sum of money to prepare for the wedding ceremony and reception. In particular, a wedding dress that is usually worn only once in a lifetime can easily cost up to tens of thousands of dollars in the market today. Moreover, interracially married couples require multiple gowns — one for each of their customs, and at least another for their reception. If interracial fusion gowns are available for these ceremonies, the entire cost of the wedding will decrease drastically. This Final Year Project attempts to create three sets of fusion wedding gowns, Motifs from different traditional wedding gowns are studied and reinterpreted for contemporary uses. These are then integrated into a wedding gown form that reflects the union of interracial couples.